Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio as prognostic markers in patients with extensive-stage small cell lung cancer treated with atezolizumab in combination with chemotherapy. Issue 15 (14th April 2023) - Kutlu, Yasin; Aydin, Sabin Goktas; Bilici, Ahmet; Oven, Bala Basak; Olmez, Omer Fatih; Acikgoz, Ozgur; Hamdard, Jamshid
Abstract : Atezolizumab is now the standard treatment for extensive-stage small cell lung cancer (ES-SCLC). Herein, we investigated the prognostic role of inflammatory markers in patients treated with atezolizumab plus chemotherapy and evaluated the efficacy and safety of adding atezolizumab to chemotherapy for patients with ES-SCLC and prognostic and predictive factors as a real-life experience. This retrospective study included 55 patients who received front-line atezolizumab with etoposide plus platin regimen for ES-SCLC. We analyzed the survival outcomes and factors that may predict response and survival. The objective response rate (ORR) was 81.8%. At a median follow-up of 23.5 months, the median progression-free survival (PFS) time was 10.8 months, and the median overall survival (OS) time was 15.2 months. In univariate analysis for PFS, limited-stage disease at the time of diagnosis, the presence of prophylactic cranial irradiation (PCI), the presence of liver metastasis, neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) were found to be prognostic factors ( P = .041, P = .034, P = .031, P = .004, and P = <.001, respectively). In other words, while the median PFS time was 14.1 months in patients with PLR ≤ 135.7, it was 7.5 months in patients with > 135.7. Similarly, median PFS was 14.9 months in patients with NLR ≤ 3.43, while it was 9.6 months in patients with > 3.43. Univariate analysis for OS revealed that limited stage at the time of diagnosis, NLR and PLR were significant prognostic indicators ( P = .01, P = .006, and P = .007, respectively). Median OS time for patients with both NLR ≤ 3.43 and PLR ≤ 135.7 was significantly better than that of patients with NLR > 3.43 and PLR > 135.7 (16.9 vs 11.3 and 16.9 vs 11.5 months, respectively). Logistic regression analysis demonstrated that PLR was an independent significant predictive factor for the response to atezolizumab plus chemotherapy (OR: 0.07, P = .028). The patients with PLR ≤ 135.7 were significantly good responders to atezolizumab plus chemotherapy treatment. Real-life data demonstrated a significant correlation between survival and NLR and, PLR in ES-SCLC patients treated with atezolizumab. In addition, PLR was a significant predictive indicator of response to atezolizumab plus chemotherapy.